Faktor – Faktor Yang Mempengaruhi Kejadian Anemia Pada Ibu Hamil di Puskesmas Juwiring - Wahyuni, Sri; Hartati, Lilik; Dynamurti Wintoro, Piscolia (Universitas Muhammadiyah Klaten, 2025)
Data on anemia cases in Central Java Province is 57.1% and anemia is mostly found in TM III pregnant women. Meanwhile, the prevalence of anemia in pregnant women in Klaten Regency is 9.19% [1]. Anemia in pregnancy is a national problem because it reflects the socio-economic welfare of society, and also has a huge influence on the quality of human resources. Pregnancy anemia is called